Constitutional fate : theory of the Constitution - Bobbitt, Philip (Oxford University Press, 1984)
Here, Philip Bobbitt studies the basis for the legitimacy of judicial review by examining six types of constitutional argument--historical, textual, structural, prudential doctrinal, and ethical--through the unusual method of contrasting sketches of prominent legal figures responding to the constitutional crises of their day. Examines the characteristic types of constitutional argument by which judicial review is carried out.